2012
DOI: 10.3109/08923973.2012.726627
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic options for patients with angioedema due to C1-inhibitor deficiencies: from pathophysiology to the clinic

Abstract: Deficiencies in the inhibitor of the first component of human complement (C1-INH) are clinically associated with both hereditary angioedema (HAE) and acquired angioedema (AAE). The reduction in C1-INH function leads to the activation of the classical complement pathway and consequent complement consumption, as well as to the activation of the contact system and the generation of bradykinin, the vasoactive peptide that increases vascular permeability and causes angioedema. The clinical features of C1-INH defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…In other studies, the C1 esterase inhibitor (C1-INH), a complement regulating factor that inactivates the C1 complex, has been utilized as a therapeutic agent for sepsis (11,12). In our previous examination, we focused on the similarity of symptoms between STSS and C1-INH deficiency, and noted that a decrease in C1-INH level caused by S. pyogenes infection is associated with the pathogenesis (13,14). In that study, we also demonstrated that streptococcal pyrogenic exotoxin B (SpeB), a representative cysteine protease from S. pyogenes, cleaves C1-INH and complement factors, including C3 and late complement factors, allowing bacterial evasion from complementmediated killing.…”
mentioning
confidence: 99%
“…In other studies, the C1 esterase inhibitor (C1-INH), a complement regulating factor that inactivates the C1 complex, has been utilized as a therapeutic agent for sepsis (11,12). In our previous examination, we focused on the similarity of symptoms between STSS and C1-INH deficiency, and noted that a decrease in C1-INH level caused by S. pyogenes infection is associated with the pathogenesis (13,14). In that study, we also demonstrated that streptococcal pyrogenic exotoxin B (SpeB), a representative cysteine protease from S. pyogenes, cleaves C1-INH and complement factors, including C3 and late complement factors, allowing bacterial evasion from complementmediated killing.…”
mentioning
confidence: 99%
“…In cases with C1-INH deficiency, the contact system becomes unstable and prone to generate kallikrein, which cleaves high molecular weight kinino-gen. Thus, the released bradykinin may function as a mediator of increased vascular permeability (8). In the present study, we focused on the similarity of these symptoms and investigated whether a S. pyogenes protease induces collapse of the complement system through C1-INH.…”
mentioning
confidence: 99%